Draft Annual Plan 2001-2002 Vol-I (Text) Government of Chhattisgarh - Planning Commission (Planning Commission, 2001)
The new State of Chhattisgarh came into existence on 1st November, 2000 with Raipur as its capital. The total geographical area of the State is 136.03 thousand sq. Kms, which is 4.11 per cent of the total area of the country. the State shares its boundaries with six States viz. Madhya Pradesh. Uttar Pradesh, Jharkhand, Orissa, Maharashtra and Andhra Pradesh. the State has 16 districts, 93 tahsils, 146 community development blocks (including 85 tribal development blocks) 97 towns and 20379 villages out of which 19720 are inhabited.
Government of Chhattisgarh, Finance, Planning, Economics and Statistics Department